(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تنحصر استخدامات الصادات الماكروليدية في الطب البيطري في مُعالجة طيف واسع من الأمراض المُعدية. يتناول هذا البحث تحديد الشروط المثلى لفصل وتحديد صادين ماكروليدين هما التايلوزين والسبيراميسين فصلاً وتحديداً متزامنين باستخدام عمودي الفصل الكرموتوغرافيينC8 و C18 والمقارنة بينهما بغية تطوير طريقة سريعة وحساسة، يُمكن اعتمادها في قياس هذين المركبين باستخدام تقانة الكروماتوغرافيا السائلة عالية الأداء وكاشف المصفوفة الديودية (High Performance Liquid Chromatography - Diode Array Detector HPLC-DAD). اعتمدت هذه الدراسة على استخدام التمليص المُتدرج Gradient Elution للطور مُتحرك، وتمًّ التوصل إلى أفضل شروط مُمكنة للفصل والتحديد مُترافقين مع أفضل زمن احتفاظ ومساحة قمة للمُركبين المدروسين باستخدام طور مُتحرك مكون من محلول مائي لفوسفات ثنائية الصوديوم الهيدروجينية اللامائية عند pH=2.4 ومحلول عضوي للأسيتونتريل بنسبة 80:20v/v (محلول A) والأسيتونتريل (محلول B) [Na2HPO4(0.04M) pH:2.4/ACN(80:20v/v)]/ACN، ودرجة حرارة 40ºC لكلا العمودين، وسرعة تدفق 1ml/min. للطور المُتحرك، وطول موجة امتصاص أعظمي280nm للتايلوزين و232nm للسبيراميسين؛ إذ سُجل أفضل مساحة قمة 5.759 للتايلوزين و5.927 للسبيراميسين عند التركيز 0.10ppm باستخدام عمود الفصل الكروماتوغرافي C8 بالمقارنة مع أفضل مساحة قمة4.432 للتايلوزين و 4.212 للسبيراميسين للتركيز نفسه باستخدام عمود الفصل الكروماتوغرافي C18، كما لوحظ تسجيل أفضل زمني احتفاظ لمُركبي التايلوزين والسبيراميسين Rt:7.013, 4.214min. على التوالي عند التركيز 0.10ppm باستخدام عمود الفصل الكروماتوغرافي C8 بالمقارنة مع أفضل زمني احتفاظ Rt:7.641, 5.898min. على التوالي عند التركيز نفسه باستخدام عمود الفصل الكروماتوغرافي C18. تميز منحني المُعايَرة لكل من مركبي التايلوزين والسبيراميسين المفصولين على عمود الفصل الكروموتوغرافي C8 بخطية جيدة ضمن مجال من التراكيز تراوح بين 0.0010-0.10ppm » 1-100ppb عند طولي الموجة λmax=280, 232nm على التوالي. Tylosin and Spiramycin are medium-spectrum macrolide antibiotic used exclusively in veterinary medicine for the treatment of a wide range of infections.This research deals with the determination of optimal conditions for simultaneous separation and determination of two macrolides antibiotics (Tylosin and Spyramicine), using C8 and C18 Chromatographic separation columns and doing the comparison between them in order to develop a rapid and sensitive method which can be used to measure these two compounds using High Performance Liquid Chromatography – Diode array detector (HPLC-DAD). This study has used the gradient elution for mobile phase and revealed that the best conditions for separation and determination are conjugated with the best retention times and best areas for both studied compounds using a mobile phase consisted of an aqueous solution of anhydrated disodium Hydrogen Phosphate at pH=2.4 and an organic solution of acetonitrile with a ratio of 80:20v/v (solution A) and acetonitrile (solution B) [Na2HPO4(0.04M) pH:2.4/CAN (80:20v/v)]/ ACN, temperature 40°C for both columns, flow ratio of 1ml/min. for the mobile phase and maximum absorption wave length 280 nm, 232nm for Tylosin and Spyramicine respectively. The best peak areas are recorded as 5.759, 5.927 for Tylosin and Spyramicine 0.10ppm respectively, using C8 Chromatographic separation column in comparison with the best peak areas 4.432, 4.212 respectively at the same concentration using C18 Chromatographic separation column. It was noticed that the best retention times for Tylosin and Spyramicine were 7.013, 4.214min. respectively at concentration of 0.10ppm using C8 Chromatographic separation column in comparison with the best retention times 7.641, 5.898min. respectively at the same concentration using C18 Chromatographic separation column. The calibration curves for both separated compounds on C8 Chromatographic separation column showed a good linearity within a concentration range of 0.0010-0.10 ppm ≈ 1-100ppb at the two wave lengths λmax. = 280, 232nm respectively.